Expression and Functional Role of Sox9 in Human Epidermal Keratinocytes - Shi, Ge (Public Library of Science, 2013)
In this study, we investigated the expression and putative role of Sox9 in epidermal keratinocyte. Immunohistochemical staining showed that Sox9 is predominantly expressed in the basal layer of normal human skin epidermis, and highly expressed in several skin diseases including psoriasis, basal cell carcinoma, keratoacanthoma and squamous cell carcinoma. In calcium-induced keratinocyte differentiation model, the expression of Sox9 was decreased in a time dependent manner. When Sox9 was overexpressed using a recombinant adenovirus, cell growth was enhanced, while the expression of differentiation-related genes such as loricrin and involucrin was markedly decreased. Similarly, when rat skin was intradermally injected with the adenovirus expressing Sox9, the epidermis was thickened with increase of PCNA positive cells, while the epidermal differentiation was decreased. Finally, UVB irradiation induced Sox9 expression in cultured human epidermal keratinocytes, and keratinocytes are protected from UVB-induced apoptosis by Sox9 overexpression. Together, these results suggest that Sox9 is an important regulator of epidermal keratinocytes with putative pro-proliferation and/or pro-survival functions, and may be related to several cutaneous diseases that are characterized by abnormal differentiation and hyperproliferation.